Transforming Character: Student Management in Cultivating the Pancasila Student Profile - Fitriyah indah Sari; Abu Yazid Adnan Qurtuby; Sollah Solehudin (Journal of Educational Management Research, 2026)
This study aims to analyze the role of student management in fostering the Pancasila Student Profile character in elementary education through the implementation of managerial functions. A qualitative case study approach was employed to obtain an in-depth understanding of student management practices in the natural school setting. Data were collected through semi-structured interviews, observations, and documentation involving the principal, teachers, and students. The data were analyzed using data reduction, data display, and conclusion drawing, while credibility was ensured through source and technique triangulation. The findings reveal that the implementation of student management effectively supports character formation through four integrated management functions: planning, organizing, actuating, and controlling. Planning was carried out by integrating character development into school programs, organizing through the distribution of responsibilities among school members, implementation through daily habituation and the Pancasila Student Profile Strengthening Project (P5), and controlling through continuous observation and character evaluation. Teacher commitment and exemplary behavior emerged as key supporting factors, whereas an unconducive classroom environment remained a significant challenge. The study implies that integrating student management functions into school practices is essential for promoting sustainable character education and strengthening the implementation of the Pancasila Student Profile in elementary schools.